Assessment of comorbid profile, quality of life and social functioning in patients with schizophrenia and schizotypal disorders - Romash, I.R. (Medicni Perspektivi, 2023)
One of the most common mental illnesses is schizophrenia and schizotypal disorders. According to the literature data, mortality among patients with schizophrenia is 1.5-2 times higher than among the general population. Patients with schizophrenia have a higher prevalence of cardiovascular disease, obesity, diabetes, osteoporosis in comparison with the general population. Such comorbid somatic diseases in the case of schizophrenia have a more acute course, a significant impact on the course of the underlying disease, the development of complications, decrease in quality of life and social functioning. The aim of the study was to study the presence and features of comorbidity, its impact on the quality of life and social functioning of patients with schizophrenia and schizotypal disorders. 100 patients were included in the study. They were divided into two groups: experimental (Group I) with schizophrenia and comparison (Group II), with other schizophrenic diseases, such as schizoaffective and schizotypal disorder. All patients were scaled according to the following methods: The Cumulative Illness Rating Scale (CIRS), Clinical Global Impression – Severity Scale (CGI-S), The Personal Social Performance Scale (PSP), CGI-S, and a short form of the questionnaire Medical Outcomes Study 36-Item Short-Form Health Status (SF-36). Charlson Index was also calculated for all patients included in the study. Due to CIRS, we detected undiagnosed comorbidity that aggravated the course of the underlying disease: 38% in Group I and 26% in Group II. The most common components in the structure of comorbidity in the patients with schizophrenia were diabetes mellitus, musculoskeletal diseases, cardiovascular diseases, non-alcoholic fatty liver disease (NAFLD). Patients with schizotypal disorders were more often diagnosed with peripheral vascular diseases, chronic lung diseases, chronic kidney diseases, and upper gastrointestinal tract disorders. A comprehensive approach to be important in the treatment of such patients. The nature and extent of comorbidity should be definitely taken into account. This will promote the compliance and improve the indicators in the examined category of patients.